2017
DOI: 10.1097/ta.0000000000001609
|View full text |Cite
|
Sign up to set email alerts
|

Early infectious outcomes after addition of fluoroquinolone or aminoglycoside to posttrauma antibiotic prophylaxis in combat-related open fracture injuries

Abstract: Background We examined combat-related open extremity fracture infections as a function of whether post-trauma antimicrobial prophylaxis included expanded Gram-negative (EGN) coverage. Methods Military personnel with open extremity fractures sustained in Iraq and Afghanistan (2009–2014) who transferred to participating hospitals in the United States were assessed. The analysis was restricted to patients with a U.S. hospitalization period of ≥7 days. Prophylaxis was classified as narrow (e.g., IV cefazolin, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
1
14
0
1
Order By: Relevance
“…They reported that there was no significant difference between treatments and the rate of infection. Lloyd et al reported that the infection rate was slightly decreased when antibiotics specifically targeting Gram-negative bacteria were selected; however, there were no significant differences in the rate of osteomyelitis [27]. Based on these results, the authors recommended cefazolin or clindamycin in open fractures.…”
Section: Table 3 Comparison Of Fractures With and Without Infectionmentioning
confidence: 99%
“…They reported that there was no significant difference between treatments and the rate of infection. Lloyd et al reported that the infection rate was slightly decreased when antibiotics specifically targeting Gram-negative bacteria were selected; however, there were no significant differences in the rate of osteomyelitis [27]. Based on these results, the authors recommended cefazolin or clindamycin in open fractures.…”
Section: Table 3 Comparison Of Fractures With and Without Infectionmentioning
confidence: 99%
“…The United States and European countries, starting from the first intervention in the field, can perform transport, first surgical interventions, and then definitive procedures and treatments of their injured military personnel under better conditions. This leads to better outcomes (3,15). On the other hand, in studies of the Sudanese and Syrian civil wars, infection, morbidity, and mortality rates are seen to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…13 Patients with open extremity fractures were excluded from this analysis and assessed separately. 14 Data were collected as part of the Trauma Infectious Disease Outcomes Study (TIDOS), which is an observational, multisite cohort study implemented to examine the short- and long-term infectious complications related to deployment-related traumatic injuries. 13 This study was approved by the Infectious Disease Institutional Review Board of the Uniformed Services University of the Health Sciences (Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%